Uji Stabilitas dan Uji Iritasi Lotion Esktrak Daun Sirih dengan Variasi Konsentrasi Trietanolamin - Desy Nawangsari; Rani Prabandari; Khamdiyah indah Kurniasih (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Triethanolamine is one of the many emulsifiers added to lotion preparations. Lotions that use triethanolamine tend to have good stability. However, the use of triethanolamine as an additive has a risk of causing irritation to the skin surface when used topically. Research on the use of betel leaf extract in topical products is known to have benefits as an antibacterial, anti-inflammatory and antioxidant. The purpose of this study was to determine the physical properties and irritant effects of betel leaf lotion using triethanolamine at a concentration of 2.5; 3 and 3.5%. The results showed that the lotion produced was homogeneous and had a thick liquid texture, spreadability was in the range of 5.37-5.83 cm, pH 7.17-7.4, adhesion 5.37-7.33 seconds and viscosity 2.312, 30 - 3,334.8 cP. The results of the stability test carried out using the cycling test method showed that the lotion preparation was stable during storage. The irritation test conducted proved that the triethanolamine used in the betel leaf extract lotion formulation did not show any irritation with a primary irritation index value of 0.0.